2014
DOI: 10.1152/ajpcell.00062.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic acid phosphatase is the main acid phosphatase with 5′-ectonucleotidase activity in the male mouse saliva and regulates salivation

Abstract: Araujo CL, Quintero IB, Kipar A, Herrala AM, Pulkka AE, Saarinen L, Hautaniemi S, Vihko P. Prostatic acid phosphatase is the main acid phosphatase with 5=-ectonucleotidase activity in the male mouse saliva and regulates salivation. Am J Physiol Cell Physiol 306: C1017-C1027, 2014. First published April 9, 2014; doi:10.1152/ajpcell.00062.2014.-We have previously shown that in addition to the well-known secreted isoform of prostatic acid phosphatase (sPAP), a transmembrane isoform exists (TMPAP) that interacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…In the next step, the primary miRNAs are further processed by an endonuclease present in the nucleus (Drosha) to the precursor miRNAs and ultimately cleaved to asymmetric duplex miRNA by an endonuclease present in the cytoplasm (Dicer)/TRBP complex. Thereupon, the RNA‐induced silencing complexes are generated, which are guided to specific mRNA and argonaute, leading to the repression of gene expression . Implications for the critical function of miRNAs in the etiology and pathogenesis of human diseases, particularly autoimmune diseases, have previously been reviewed …”
Section: Noncoding Rnas In Ra Flssmentioning
confidence: 99%
See 1 more Smart Citation
“…In the next step, the primary miRNAs are further processed by an endonuclease present in the nucleus (Drosha) to the precursor miRNAs and ultimately cleaved to asymmetric duplex miRNA by an endonuclease present in the cytoplasm (Dicer)/TRBP complex. Thereupon, the RNA‐induced silencing complexes are generated, which are guided to specific mRNA and argonaute, leading to the repression of gene expression . Implications for the critical function of miRNAs in the etiology and pathogenesis of human diseases, particularly autoimmune diseases, have previously been reviewed …”
Section: Noncoding Rnas In Ra Flssmentioning
confidence: 99%
“…Thereupon, the RNA-induced silencing complexes are generated, which are guided to specific mRNA and argonaute, leading to the repression of gene expression. 111 Implications for the critical function of miRNAs in the etiology and pathogenesis of human diseases, particularly autoimmune diseases, have previously been reviewed. 34 The aberrant expression level of several miRNAs has been identified through profiling the expression pattern of FLSs from RA and OA patients and healthy controls.…”
Section: Noncoding Rnas In Ra Flss Long Noncoding Rnas In Ra Flssmentioning
confidence: 99%
“…The knockout prostates at this age contained more B cells than wild type prostates (6.6 ± 0.2% versus 1.4 ± 0.9%, P = 0.004). Also salivary glands contain more immune cells in these male mice, when they are young, but the difference disappears with aging [31]. The practically nonexisting alterations of major immune cell subpopulations in absence of PAP suggest that PAP does not seem to have any marked role in the immune system or its absence is compensated by CD73.…”
Section: Resultsmentioning
confidence: 99%
“…However, the expression of PAP in prostate cancer tissue has been shown to be reduced . The studies carried out in our PAP‐knockout mouse model showed that a deficiency in the expression of PAP leads to the development of prostate adenocarcinoma , increased acinar cell proliferation in the submandibular salivary glands (SMGs) and disturbed neurotransmitter signaling in the brain . The common characteristic amongst these organs is that the epithelial cells as well as neurons are polar secretory cells.…”
Section: Introductionmentioning
confidence: 99%